2021
DOI: 10.11591/ijere.v10i3.21389
|View full text |Cite
|
Sign up to set email alerts
|

Elementary students’ attitudes towards STEM and 21st-century skills

Abstract: <span>Science, Technology/Engineering and Math (STEM) and 21st-century learning are very important to be applied to all students starting from their early age, including at the elementary school level. This study aimed to describe students' attitudes towards STEM and 21st-century skills according to gender and education level. This research was descriptive quantitative by explaining and comparing the results of the questionnaires given to students. Student attitudes were described based on domain of STEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…According to the study, girls' "Learning and Innovation Skills," "Life and Career Skills," and total scores were higher than they were when they were younger. A review of the literature revealed that studies with various age groups did not show any statistically significant gender differences (Dinler, Simsar, & Yalçn, 2021;Elci, 2021;Gurultu, Aslan, & Alci, 2020;Perdana et al, 2021;Uyar & Cicek, 2021). In their study of the seventhgrade students' 21st-century talents, Rogayan et al (2021) discovered that female students had greater scores than male students.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…According to the study, girls' "Learning and Innovation Skills," "Life and Career Skills," and total scores were higher than they were when they were younger. A review of the literature revealed that studies with various age groups did not show any statistically significant gender differences (Dinler, Simsar, & Yalçn, 2021;Elci, 2021;Gurultu, Aslan, & Alci, 2020;Perdana et al, 2021;Uyar & Cicek, 2021). In their study of the seventhgrade students' 21st-century talents, Rogayan et al (2021) discovered that female students had greater scores than male students.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…The purpose of the study by Michael and Alsup (2016) was to determine whether boys and females in a Protestant Christian middle school setting had different attitudes about STEM courses. This study (Perdana et al, 2021) aims to evaluate the attitudes of students in primary school in relation to 21st-century abilities, gender, and grade level. The goal of research by Sachdev and Eamoraphan (2020) was to see if there were any gender-related differences in teachers' attitudes toward STEM education.…”
Section: The Aims Of Studiesmentioning
confidence: 99%
“…According to the results of the study in which university-level students participated, students' attitudes toward STEM were positive (Altakahyneh & Abumusa, 2020;Kartal & Taşdemir, 2021), and at moderate level among pre-university students (Perdana et al, 2021). It has been demonstrated that while they faced doubt in the other aspects (Science and Technology), they had more favorable opinions concerning mathematics and engineering (Anastasiadis & Zirinoglou, 2022).…”
Section: Relations Among Attitudes Toward Stem and Variablesmentioning
confidence: 99%
“…The student's average score was 56.78 which place their level of proficiency in 21st-century skills in the low range. (Abualrob, 2019;Asrizal, Yurnetti, & Usman, 2022;Jannah, Prasojo, & Jerusalem, 2020;Perdana, Apriani, Richardo, Rochaendi, & Kusuma, 2021;Putra, Wiyanto, & Linuwih, 2020;Rochmawati, Wiyanto, & Ridlo, 2019). In order to enhance the 21st century skills of those students, this problems need to be handled as the primary school children have a significant role in future.…”
Section: Introductionmentioning
confidence: 99%